Synthetic, Structural and Antimicrobial Studies of Some Transition Metals Heterocyclic Complexes of Bio-inorganic Relevance - Gupta, S.K.; Sharma, R.C.; Gupta, A.K. (Asian Journal of Chemistry, 2010)
1 : 1 : 1, M(II)-dipy-multidentate ligand, mixed ligand complexes were synthesised and characterized by elemental analysis, IR and UV spectral studies, magnetic and conductivity measurements [where, M═Co(II), Ni(II) and Cu(II); dipy═4,4´ -dipyridyl and multidentate ligand═2-mercaptobenzoic acid (MBA) and 3,5-dinitrosalicylic acid (DNSA)]. The compounds have been screened for their antimicrobial activity on gram +ve bacteria (Staphylococcus aureus) and gram –ve bacteria (Escherichia coli) at 32ºC for 48 hrs and fungi (Aspergillus niger and fumigatus) by serial dilution method at 32ºC for 7 days.